The Role of the Drug and Food Control Agency (BPOM) in Addressing the Distribution of Illegal Cosmetics - Christi, Novi; Soemartono , Gatot P. (Jurnal Ilmu Hukum Kyadiren, 2024)
The beauty industry, while fostering cosmetic advancements, also creates opportunities for unauthorized individuals to market products. This study assesses consumer protection and The Drug and Food Control Agency (BPOM)’s oversight of illicit cosmetics sales. Employing a normative juridical approach with secondary data analysis and a statute and case methodology, the research examines existing legal frameworks. The analysis reveals that Indonesian law, notably Article 142 of the health Law and related statutes, provides legal safeguards for consumers. Violations, such as sales without proper distribution permits, incur civil, administrative, and criminal penalties. BPOM bears the responsibility of monitoring cosmetics distribution but is frequently criticized for negligence. To mitigate this, BPOM should intensify routine and proactive inspections to curb illegal product circulation and uphold community safety standards.